The Influence of Decisional and Emotional Forgiveness on Attributions - Lichtenfeld, Stephanie; Maier, Markus A.; Buechner, Vanessa L.; Fernández Capo, Maria (Frontiers in Psychology, 2019)
Research on forgiveness suggests that forgiveness is an emotion-focused coping process important for clinical settings as it can promote both physical and mental health (Worthington et al., 2005; Witvliet and McCullough, 2007). Investigating antecedents of forgiveness, empirical studies and theoretical models propose that attributions influence forgiveness. However, hardly any studies or theoretical models have ever looked at the possibility that this relationship may be reciprocal in nature and whether forgiveness also impacts a victim’s attributions has not been investigated. The present, highly powered (n = 969) study seeks to fill this gap and provides the first empirical support that emotional forgiveness has a strong influence on subsequent attributions. Specifically, individuals, who have emotionally forgiven a transgression, hold the transgressor less responsible for the offense compared to those in the decisional forgiveness and control condition. Moreover, the findings conceptually replicate previous research (Lichtenfeld et al., 2015) by demonstrating that emotional, but not decisional forgiveness affects cognition and, thus, emotional and decisional forgiveness should be treated as distinct facets in the forgiveness process. Implications of these results for clinical and health psychology are discussed.